Aspiration of tracheoesophageal prosthesis in a laryngectomized patient - Conte, Sergio C; De Nardi, Elena; Conte, Federico; Nardini, Stefano (Multidisciplinary respiratory medicine, 2012)
Background The voice prosthesis inserted into a tracheoesophageal fistula has become the most widely used device for voice rehabilitation in patients with total laryngectomy. Case presentation We describe a case of tracheoesophageal prosthesis’ (TEP) aspiration in a laryngectomized patient, with permanent tracheal stoma, that appeared during standard cleaning procedure, despite a programme of training for the safe management of patients with voice prosthesis. Conclusions The definitive diagnosis and treatment were performed by flexible bronchoscopy, that may be considered the procedure of choice in these cases, also on the basis of the literature.